Research on the Pore Evolution of Sandstone in Cold Regions under Freeze-Thaw Weathering Cycles Based on NMR - Zheng Pan; Keping Zhou; Rugao Gao; Zhen Jiang; Chun Yang; Feng Gao (Geofluids)
The evolution of the rock pore structure is an important factor influencing rock mechanical properties in cold regions. To study the mesoscopic evolution law of the rock pore structure under freeze-thaw weathering cycles, a freeze-thaw weathering cycle experiment was performed on red sandstone from the cold region of western China with temperatures ranging from -20°C to +20°C. The porosity, T2 spectral distribution, and magnetic resonance imaging (MRI) characteristics of the red sandstone after 0, 20, 40, 60, 80, 100, and 120 freeze-thaw weathering cycles were measured by the nondestructive detection technique nuclear magnetic resonance (NMR). The results show that the porosity of sandstone decreases first and then increases with the increase of the freeze-thaw weathering cycles and reaches the minimum at 60 of freeze-thaw weathering cycles. The evolution characteristics of porosity can be divided into three stages, namely, the abrupt decrease in porosity, the slow decrease in porosity, and the steady increase in porosity. The evolution characteristics of the T2 spectrum distribution, movable fluid porosity (MFP), and MRI images in response to the freeze-thaw weathering process are positively correlated with the porosity. Analysis of the experimental data reveals that the decrease in the porosity of the red sandstone is mainly governed by mesopores, which is related to the water swelling phenomenon of montmorillonite. Hence, the pore connectivity decreases. As the number of freeze-thaw cycles increases, the effect of the hydrophysical reaction on the porosity gradually disappears, and the frost heaving effect caused by the water-ice phase transition gradually dominates the pore evolution law of red sandstone.